2006
DOI: 10.3171/foc.2006.21.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Participation in contact or collision sports in athletes with epilepsy, genetic risk factors, structural brain lesions, or history of craniotomy

Abstract: ✓Despite a plethora of guidelines for return to play following mild head injury, a discussion of when and if an athlete should be allowed to participate in contact or collision sports if he or she sustains a structural brain lesion or after a head injury requiring craniotomy is lacking. The structural lesions discussed include arachnoid cyst, Chiari malformation Type I, cavum septum pellucidum, and the presence of ventriculoperitoneal shunts. Issues unique to this population with respect to the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 84 publications
(94 reference statements)
0
41
0
Order By: Relevance
“…Over the years, several authors have offered recommendations about when athletes should be advised to retire from contact or collision sports, but most have focused on collegiate and professional athletes. 16,18,20,21,23,43,66,76,91,93 Although some authors suggest a more conservative approach should be applied to child and adolescent athletes, 16,23 indications for retirement from sports remain controversial and there are limited reports that discuss these issues in application to pediatric SRC patients. Because decisions regarding athlete retirement are complex and must be tailored to the individuals in the absence AbbreviAtioNs CTE = chronic traumatic encephalopathy; PCS = postconcussion syndrome; RTP = return to play; SCI = spinal cord injury; SCIWORA = SCI without radiographic abnormality; SRC = sports-related concussion; TBI = traumatic brain injury.…”
Section: Neurosurg Focus 40 (4):e8 2016mentioning
confidence: 99%
See 4 more Smart Citations
“…Over the years, several authors have offered recommendations about when athletes should be advised to retire from contact or collision sports, but most have focused on collegiate and professional athletes. 16,18,20,21,23,43,66,76,91,93 Although some authors suggest a more conservative approach should be applied to child and adolescent athletes, 16,23 indications for retirement from sports remain controversial and there are limited reports that discuss these issues in application to pediatric SRC patients. Because decisions regarding athlete retirement are complex and must be tailored to the individuals in the absence AbbreviAtioNs CTE = chronic traumatic encephalopathy; PCS = postconcussion syndrome; RTP = return to play; SCI = spinal cord injury; SCIWORA = SCI without radiographic abnormality; SRC = sports-related concussion; TBI = traumatic brain injury.…”
Section: Neurosurg Focus 40 (4):e8 2016mentioning
confidence: 99%
“…76 Finally, several authors have suggested that patients with symptomatic or pain-causing lesions at the level of the foramen magnum, including Chiari malformations, be considered for retirement from contact and collision sports. 20,76,93 These recommendations largely stem from rare reports of sudden death among patients with Chiari malformations exposed to minor head trauma, and from speculation that medullary compression could have accounted for these outcomes. 76 A recent retrospective cohort study, however, demonstrated an exceedingly low risk of future catastrophic injury during sports participation in children with Chiari I malformation, even after foramen magnum decompression.…”
Section: Neurological Surgeons and The Congress Of Neurologicalmentioning
confidence: 99%
See 3 more Smart Citations